Wearable Technology in the Perioperative Period: Predicting Risk of Postoperative Complications in Patients Undergoing Elective Colorectal Surgery. Issue 4 (April 2020) - Hedrick, Traci L.; Hassinger, Taryn E.; Myers, Emma; Krebs, Elizabeth D.; Chu, David; Charles, Ashley N.; Hoang, Sook C.; Friel, Charles M.; Thiele, Robert H.
Abstract : BACKGROUND: The implementation of protocolized care pathways has resulted in major improvements in surgical outcomes. Additional gains will require focused efforts to alter preexisting risk. Prehabilitation programs provide a promising avenue for risk reduction. OBJECTIVE: This study used wearable technology to monitor activity levels before colorectal surgery to evaluate the impact of preoperative activity on postoperative outcomes. DESIGN: This was a prospective nonrandomized observational study. SETTINGS: The study was conducted at a large academic medical center. PATIENTS: Patients undergoing elective colorectal surgery from January 2018 to February 1, 2019, were included. MAIN OUTCOME MEASURES: Patients were trained in the usage of wearable activity-tracking devices and instructed to wear the device for 30 days before surgery. Patients were stratified as active (≥5000 steps per day) and inactive (<5000 steps per day) based on preoperative step counts. Univariate analyses compared postoperative outcomes. Multivariable regression models analyzed the impact of preoperative activity on postoperative complications, adjusting for each patient's baseline risk as calculated using the American College of Surgeons National Surgical Quality Improvement Program Surgical Risk Calculator. Models were rerun without the addition of activity and the predictive ability of the models compared. RESULTS: Ninety-nine patients were included, with 40 (40.4%) classified as active. Active patients experienced fewer overall complications (11/40 (27.5%) vs 33/59 (55.9%); p = 0.005) and serious complications (2/40 (5%) vs 12/59 (20.3%); p = 0.032). Increased preoperative activity was associated with a decreased risk of any postoperative complication (OR = 0.386; p = 0.0440) on multivariable analysis. The predictive ability of the models for complications and serious complications was improved with the addition of physical activity. LIMITATIONS: The study was limited by its small sample size and single institution. CONCLUSIONS: There is significant room for improvement in baseline preoperative activity levels of patients undergoing colorectal surgery, and poor activity is associated with increased postoperative complications. These data will serve as the basis for an interventional trial investigating whether wearable devices help improve surgical outcomes through a monitored preoperative exercise program. See Video Abstract at http://links.lww.com/DCR/B145 . TECNOLOGÍA PORTÁTIL EN EL PERÍODO PERIOPERATORIO: PREDICCIÓN DEL RIESGO DE COMPLICACIONES POSTOPERATORIAS EN PACIENTES SOMETIDOS A CIRUGÍA COLORRECTAL ELECTIVA: ANTECEDENTES: La implementación de vías de atención protocolizadas ha dado lugar a importantes mejoras en los resultados quirúrgicos. Para obtener más beneficios será necesario realizar esfuerzos concentrados para modificar el riesgo preexistente. Los programas de rehabilitación proporcionan una vía prometedora para la reducción del riesgo. OBJETIVO: Este estudio utilizó tecnología portátil para monitorear los niveles de actividad antes de la cirugía colorrectal para evaluar el impacto de la actividad preoperatoria en los resultados postoperatorios. DISEÑO: Estudio observacional prospectivo no aleatorizado. AJUSTES: Gran centro médico académico. PACIENTES: Pacientes sometidos a cirugía colorrectal electiva desde enero de 2018 hasta el 1 de febrero de 2019. PRINCIPALES MEDIDAS DE RESULTADO: Los pacientes fueron entrenados en el uso de dispositivos portátiles para el seguimiento de la actividad y se les indicó usar el dispositivo durante 30 días antes de la cirugía. Los pacientes fueron estratificados como activos (> 5000 pasos / día) e inactivos (<5000 pasos / día) en base a los recuentos de pasos preoperatorios. Los análisis univariados compararon los resultados postoperatorios. Los modelos de regresión multivariable analizaron el impacto de la actividad preoperatoria en las complicaciones postoperatorias, ajustando el riesgo de referencia de cada paciente según lo calculado utilizando la Calculadora de riesgo quirúrgico del Programa Nacional de Mejora de la Calidad Quirúrgica del Colegio Americano de Cirujanos. Los modelos se volvieron a ejecutar sin agregar actividad, y se comparó la capacidad de predicción de los modelos. RESULTADOS: Noventa y nueve pacientes fueron incluidos con 40 (40.4%) clasificados como activos. Los pacientes activos experimentaron menos complicaciones generales [11/40 (27, 5%) frente a 33/59 (55, 9%); p = 0, 005] y complicaciones graves [2/40 (5%) frente a 12/59 (20, 3%); p = 0, 032]. El aumento de la actividad preoperatoria se asoció con una disminución del riesgo de cualquier complicación postoperatoria (OR 0.386, p = 0.0440) en el análisis multivariable. La capacidad predictiva de los modelos para complicaciones y complicaciones graves mejoró con la adición de actividad física. LIMITACIONES: Tamaño de muestra pequeño, una sola institución. CONCLUSIONES: Existe un margen significativo para mejorar los niveles basales de actividad preoperatoria de los pacientes de cirugía colorrectal, y la escasa actividad se asocia con mayores complicaciones postoperatorias. Estos datos servirán de base para un ensayo intervencionista que investigue si los dispositivos portátiles ayudan a mejorar los resultados quirúrgicos a través de un programa de ejercicio preoperatorio monitoreado. Consulte Video Resumen en http://links.lww.com/DCR/B145 .